2002
DOI: 10.1016/s0022-0981(02)00235-6
|View full text |Cite
|
Sign up to set email alerts
|

Influence of nitrogen enrichment on size-fractionated in vitro carboxylase activities of phytoplankton from Thau Lagoon (Coastal Mediterranean Lagoon, France)

Abstract: The influence of dissolved inorganic and organic nitrogen (DIN and DON) enrichments on pools of enzymes responsible for CO 2 fixation by the Calvin-Benson (Rubisco) and β-carboxylation pathways (β-carboxylases) were studied in a natural plankton assemblage. The plankton community from a coastal Mediterranean lagoon were incubated in situ for 24 h with initially ammonium, nitrate and DON (taurine) enrichments and compared to a control without any enrichment. An increase of small picophytoplankton and diatom bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 52 publications
0
4
0
1
Order By: Relevance
“…5). This may be explained by the very high biomass specific carbon production of small picoeukaryote cells previously measured in this coastal lagoon [9] which were dominated by the small picoeukaryote Ostreococcus tauri (-green flagellate‖ pigment markers) throughout the year [36].…”
Section: Discussionmentioning
confidence: 89%
“…5). This may be explained by the very high biomass specific carbon production of small picoeukaryote cells previously measured in this coastal lagoon [9] which were dominated by the small picoeukaryote Ostreococcus tauri (-green flagellate‖ pigment markers) throughout the year [36].…”
Section: Discussionmentioning
confidence: 89%
“…Different fractions of whole water were mixed with filtered water to obtain five serial dilutions (0.15, 0.25, 0.45, 0.75 and 1.0 unfiltered water) in duplicate 1L PC bottles. Each bottle received a nutrient enrichment based on K medium (Keller et al, 1987) resulting in a final nitrate concentration of 10 µM, which had been previously verified to be sufficient to satisfy phytoplankton nitrogen demands over 24 h (Fouilland et al, 2002). All other nutrients contained in K medium were added in stoichiometric proportions to the original K composition.…”
Section: Methodsmentioning
confidence: 99%
“…Human activities have significantly increased the input of nitrate and phosphate nutrients into coastal waters, while the silicate concentration has remained constant or even decreased in terrestrial freshwater discharges. This has affected the distribution of diatoms, FOUILLAND et al (2002), demonstrated an increase of small picophytoplankton and diatom biomass in the enriched inorganic nitrogen treatments in a Mediterranean lagoon. EGGE (1998) reported that diatoms were not able to dominate when phosphate was deficient, although silicate and nitrate were in excess.…”
Section: Species Response To Nutrient Variabilitymentioning
confidence: 99%